Utilization of an Electronic Medical Record–integrated Dashboard Improves Identification and Treatment of Anemia and Iron Deficiency in Pediatric Inflammatory Bowel Disease. Issue 9 (9th November 2020) - Breton, Jessica; Witmer, Char M; Zhang, Yuchen; Downing, Maura; Stevenson, Jamie; McDermott, Janine; Siddique, Shazia M; Grossman, Andrew B
Abstract: Background: Iron deficiency (ID) and anemia are one of the most common extraintestinal manifestations of inflammatory bowel disease (IBD), usually complicating the course both in ulcerative colitis and Crohn's disease. Despite their high prevalence and significant impact on patients, this particular aspect is still underestimated by clinicians. Although guidelines have been recently published to address this problem, these recommendations do not address pediatric specific concerns and do not provide guidance as to how implement these guidelines in clinical practice. The aims of this quality improvement (QI) initiative were to improve the rates of detection and treatment of anemia in children with IBD. Methods: After the creation of a multidisciplinary team of skateholders in IBD and anemia, we launched a multifaceted QI strategy that included the development of a pediatric evidence-based care pathway, utilization of an electronic medical record (EMR)-integrated dashboard to track patients, and generation of an automated provider-based monthly report. Data were collected and graphed into statistical process control charts. Results: These key strategies resulted in improved rates of ID screening from 31.7% to 63.6%, in increased treatment rates from 38.2% to 49.9%, and in decreased prevalence of anemia from 35.8% to 29.7%, which was reflected by a greater decline in patients with quiescent disease. Conclusions: Quality improvement strategies incorporating the creation of a pediatric evidence-based care pathway with an EMR-supported electronic dashboard were the foundation of a successful intervention in the management of ID and anemia in pediatric IBD. Our positive results demonstrate the potential of QI initiatives using automated technology to assist clinicians in their commitment to provide evidence-based IBD care and enhance patient outcomes.